Values, Ideologies, and Frames of Reference in Employment Relations - BUDD, John W. (Institutional Knowledge at Singapore Management University, 2008)
Employment relations—which form most of the 20th century was called industrial relations, and what some now call human resources and industrial relations—is a multidisciplinary field studying all aspects of work and the employment relationship (Ackers and Wilkinson, 2003; Budd, 2004; Kaufm an, 2004). A multidisciplinary approach means that competing values and assumptions underlie the analyses, policies, and practices of employment relations scholars, practitioners, and policymakers. Unfortunately, these underlying beliefs are often implicit rather than explicit, or, with the longstanding focus on how industrial relations processes work, sometimes ignored altogether. But understanding the employment relationship, corporate human resource management practices, labor union strategies, and work-related public policies and laws requires understanding how values and assumptions form the ideologies and frames of reference used by scholars, practitioners, and policymakers.